Determinants of CoRNR-Dependent Repression Complex Assembly on Nuclear Hormone Receptors - Hu, Xiao (American Society for Microbiology, 2001)
Ligand-dependent exchange of coactivators and corepressors is the fundamental regulator of nuclear hormone receptor (NHR) function. The interaction surfaces of coactivators and corepressors are similar but distinct enough to allow the ligand to function as a switch. Multiple NHRs share features that allow corepressor binding, and each of two distinct corepressors (N-CoR and SMRT) contains two similar CoRNR motifs that interact with NHRs. Here we report that the specificity of corepressor-NHR interaction is determined by the individual NHR interacting with specific CoRNR boxes within a preferred corepressor. First, receptors have distinct preferences for CoRNR1 versus CoRNR2. For example, the retinoic acid receptor binds CoRNR1, while RXR interacts almost exclusively with CoRNR2. Second, the NHR preference for N-CoR or SMRT is due to differences in CoRNR1 but not CoRNR2. Moreover, within a single corepressor, affinity for different NHRs is determined by distinct regions flanking CoRNR1. The highly specific determinants of NHR-corepressor interaction and preference suggest that repression is regulated by the permissibility of selected receptor-CoRNR-corepressor combinations. Interestingly, different NHR surfaces contribute to binding of CoRNR1 and CoRNR2, suggesting a model to explain corepressor binding to NHR heterodimers.